New Replica Selection Technique for Binding Replica Sites in Data Grids - Almuttairi, Rafah M.; Wankar, Rajeev; Negi, Atul; Rao, C. R.; Almahna, Mahdi S. (Iraqi Journal for Electrical and Electronic Engineering, 2010)
The objective in Data Grids is to reduce access and file (replica) transfer latencies, as well as to avoid single site congestion by the numerous requesters. To facilitate access and transfer of the data, the files of the Data Grid are distributed across the multiple sites. The effectiveness of a replica selection strategy in data grids depends on its ability to serve the requirement posed by the users' jobs. Most jobs are required to be executed at a specific execution time. To achieve the QoS perceived by the users, response time metrics should take into account a replica selection strategy. Total execution time needs to factor latencies due to network transfer rates and latencies due to search and location. Network resources affect the speed of moving the required data and searching methods can reduce scope for replica selection. This paper presents a replica selection strategy that adapts its criteria dynamically so as to best approximate application providers’ and clients’ requirements. We introduce a new selection technique (EST) that shows improved performance over the more common algorithms.